Zinc Removal from ZnO Industrial Wastewater by Hydroxide Precipitation and Coagulation Methods: The Role of pH and Coagulant Dose - Ratnawati Ratnawati; Marcelinus Christwardana; Sudirman Sudirma; Enjarlis Enjarlis (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2020)
Liquid waste from the ZnO industry must be treated to meet the quality standards of wastewater into water bodies, according to the Minister of Environment Regulations No.5, 2014. It still contains 79 mg/L of Zn metal, cloudy with turbidity above 500 NTU, and COD value around 222 mg/L. This study aims to determine the effect of pH on reducing Zn metal and the coagulant dose to minimize turbidity and COD in liquid waste produced by the ZnO factory in Depok, West Java. The waste treatment has been carried out by adding alkaline to neutralize the acid conditions in the equalization basin. However, the results have not met the requirements. It is necessary to vary the pH (8.5; 9.0; 9.5; 10.0 and 10.5) to precipitate of Zn optimally, modify the dose of coagulants (50; 100 and 150 mg/L) and reaction times (10; 15 and 20 minutes) to reduce its turbidity and COD concentration. The best results were obtained at a pH of 9.5 with a coagulant dose of 50 mg/L and a reaction time of 10 minutes. This condition can reduce Zn concentration (79 to 3.71 mg/L), turbidity (557 to 1.42 NTU), COD (222 to 68 mg/L) with a removal efficiency of 95.3%; 99.7%; and 69.4% respectively. These values have met the standard requirements according to government regulations.